2021
DOI: 10.21203/rs.3.rs-159109/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of Three Chalcone Synthase-like Genes in Dianthus Chinensis 

Abstract: Being an important garden plant, Dianthus chinensis flower has a great variety of colors and color patterns. Chalcone synthase (CHS) is the key enzyme in the anthocyanin biosynthetic pathway. Although CHS genes have been isolated and characterized in ornamental plants, the CHS gene is still unknown in D. chinensis. In our study, three CHS genes, DchCHS1 (KX893854), DchCHS2 (MK404175) and DchCHS3 (MK416198) were isolated in D. chinensis. Their deduced amino acid sequences show high homology with the known CHS … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Mahon et al (2021) in their study have reported that the induction of the chalcone synthetase 3 (CHS3) gene in transgenic poplar increased the accumulation of flavonoid naringenin in methanolic extracts of xylem compared to wild-type trees 26 . The CHS gene is widely isolated and characterized from many types of plants 27 31 . Besides genetic manipulations, the production of appropriate secondary metabolites requires the molecules triggering the production, because the biosynthetic pathway of the secondary metabolites is a part of the plant's defense mechanism against pathogens and herbivores.…”
Section: Introductionmentioning
confidence: 99%
“…Mahon et al (2021) in their study have reported that the induction of the chalcone synthetase 3 (CHS3) gene in transgenic poplar increased the accumulation of flavonoid naringenin in methanolic extracts of xylem compared to wild-type trees 26 . The CHS gene is widely isolated and characterized from many types of plants 27 31 . Besides genetic manipulations, the production of appropriate secondary metabolites requires the molecules triggering the production, because the biosynthetic pathway of the secondary metabolites is a part of the plant's defense mechanism against pathogens and herbivores.…”
Section: Introductionmentioning
confidence: 99%